2020
DOI: 10.7150/ijbs.32331
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Wnt/β-catenin signaling in patients with Stevens-Johnson syndrome and toxic epidermal necrolysis

Abstract: Stevens-Johnson syndrome (SJS) and toxic epidermal necrosis (TEN) are rare but life-threatening severe cutaneous adverse reactions. Current studies have suggested that the pathobiology of drug-mediated SJS/TEN involves a dysregulation of cellular immunity with overwhelming activation of cytotoxic T lymphocytes. The canonical Wnt signaling pathway plays important roles in T cell development and activation, which may provide potential avenues for alleviating dysregulated immunity in SJS/TEN. In this study, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Blocking circulating retinoids could mitigate the symptoms of SJS/TEN ( Mawson et al, 2015 ). A study showed Wnt signaling was downregulated in drug-induced SJS/TEN, and enhancement of Wnt signaling attenuated ex vivo activation of drug-specific T cells from SJS/TEN patients ( Chen et al, 2020 ). Plus, using metabonomics to study the metabolites might be helpful to identify the common etiology to cause SJS/TEN.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Blocking circulating retinoids could mitigate the symptoms of SJS/TEN ( Mawson et al, 2015 ). A study showed Wnt signaling was downregulated in drug-induced SJS/TEN, and enhancement of Wnt signaling attenuated ex vivo activation of drug-specific T cells from SJS/TEN patients ( Chen et al, 2020 ). Plus, using metabonomics to study the metabolites might be helpful to identify the common etiology to cause SJS/TEN.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%